Uruguay : Second Review Under the Stand-By Arrangement, and Request for Waiver of a Performance Criterion-Staff Report; and News Brief on Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2001)
Uruguay is facing a third year of negative output growth. It, however, is making progress with economic adjustment. The government has taken a calculated risk by doubling the pace of depreciation of the exchange rate band. The government is committed to strengthening the underlying fiscal position in 2002 and the medium term for a turnaround in the debt/GDP ratio. Measures such as the public sector banks need to be reformed. The deregulation of the economy and providing additional opportunities for private sector investment are being taken up.